A user-centered, iterative engineering approach for advanced biomass cookstove design and development. (15th September 2017) - Shan, Ming; Carter, Ellison; Baumgartner, Jill; Deng, Mengsi; Clark, Sierra; Schauer, James J; Ezzati, Majid; Li, Jiarong; Fu, Yu; Yang, Xudong
Abstract: Unclean combustion of solid fuel for cooking and other household energy needs leads to severe household air pollution and adverse health impacts in adults and children. Replacing traditional solid fuel stoves with high efficiency, low-polluting semi-gasifier stoves can potentially contribute to addressing this global problem. The success of semi-gasifier cookstove implementation initiatives depends not only on the technical performance and safety of the stove, but also the compatibility of the stove design with local cooking practices, the needs and preferences of stove users, and community economic structures. Many past stove design initiatives have failed to address one or more of these dimensions during the design process, resulting in failure of stoves to achieve long-term, exclusive use and market penetration. This study presents a user-centered, iterative engineering design approach to developing a semi-gasifier biomass cookstove for rural Chinese homes. Our approach places equal emphasis on stove performance and meeting the preferences of individuals most likely to adopt the clean stove technology. Five stove prototypes were iteratively developed following energy market and policy evaluation, laboratory and field evaluations of stove performance and user experience, and direct interactions with stove users. The most current stove prototype achieved high performance in the field on thermal efficiency (ISO Tier 3) and pollutant emissions (ISO Tier 4), and was received favorably by rural households in the Sichuan province of Southwest China. Among household cooks receiving the final prototype of the intervention stove, 88% reported lighting and using it at least once. At five months post-intervention, the semi-gasifier stoves were used at least once on an average of 68% [95% CI: 43, 93] of days. Our proposed design strategy can be applied to other stove development initiatives in China and other countries.